2020
DOI: 10.1108/ijilt-02-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Teachers calling for organizational support to digitalize teaching

Abstract: PurposeThe digitalization of society places new demands on education. It is apparent since most countries have introduced curricula requirements to digitalize teaching. This study examines the organizational support teachers need to digitalize teaching. The study is being conducted in Sweden because they have experienced challenges with the introduction of new national digitalization requirements. Thus, this study explores the following research question: What organizational support do Swedish teachers describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Digital transformation in higher education institutions encourages lecturers to think about and implement digital technology in learning [31] in collaborative manner [32]. They are required to improve their competence and develop technologybased learning media.…”
Section: Lecturer Readiness For Digital Transformationmentioning
confidence: 99%
“…Digital transformation in higher education institutions encourages lecturers to think about and implement digital technology in learning [31] in collaborative manner [32]. They are required to improve their competence and develop technologybased learning media.…”
Section: Lecturer Readiness For Digital Transformationmentioning
confidence: 99%
“…They have revealed that active participation in the classroom increased due to the individual approach and the use of digital media. Correspondingly, technology-supported learning personalization changes classroom management practices and strengthens teacher-student collaboration as well as peer-to-peer collaboration [47]. A national study in the United States focused on the systematical examination of the use of technology and the needs of teachers based on the conceptual framework of the Personalized Integrated Education System (PIES) has found that today 308 student-oriented schools in the country meet at least three of the five criteria for personalized learning.…”
Section: International Experiencementioning
confidence: 99%
“…At the application level, it is typically represented by "new retail" and "new manufacturing." It has brought enormous economic benefits and increasingly become a new driving force for economic growth, while also having a profound impact on environmental sustainability (Leino Lindell, 2020). The so-called green economy is a new economic form developed with market orientation, traditional industrial economy as the foundation, and harmony between economy and environment as the goal.…”
Section: Introductionmentioning
confidence: 99%